Governance Composition of Board Directors and Audit Committees: Gender Diversity Moderation in Sustainability Reporting - Hasna Nur Fadlilah; Frido Saritua Simatupang (Summa : Journal of Accounting and Tax, 2026)
This study analyzes the influence of the board of directors and audit committee on sustainability report disclosure, with gender diversity as a moderating variable in financial sector companies listed on the Malaysian Stock Exchange during the period 2022–2024. The background of this study is the increasing demand for sustainability transparency in line with regulatory pressure and stakeholder attention to environmental and social issues. However, previous studies have shown inconsistent findings regarding the role of corporate governance mechanisms in encouraging sustainability reporting disclosure, prompting this study to add gender diversity as a moderating variable. This study uses a quantitative approach with secondary data sources from annual reports and sustainability reports of 15 companies selected through purposive sampling. The analysis was conducted using panel data regression and Moderated Regression Analysis (MRA) with the help of Eviews 13. The results show that, to a certain extent, sustainability report disclosure is not influenced by the board of directors or the audit committee. Furthermore, gender diversity does not enhance the relationship between corporate governance mechanisms and sustainability report disclosure in the study period. These results indicate that the effectiveness of governance in promoting sustainability practices is not solely determined by the size of the structure or the proportion of women on the board of directors, but is also influenced by the quality of the board's role and involvement in sustainability oversight.